Effect of pulse frequency and current density on anomalous composition and nanomechanical property of electrodeposited Ni–Co films - Chung, C.K.; Chang, W.T. (Thin solid films, 2009)
Effect of pulse frequency and current density on the anomalous cobalt content and nanomechanical property of the electrodeposited nickel–cobalt (Ni–Co) films has been investigated. The composition, morphology, phase and hardness of the Ni–Co alloy films were examined by scanning electron microscope with an attached energy dispersive X-ray spectroscope, X-ray diffraction and nanoindentation techniques, respectively. The different Co composition of the Ni–Co films codeposited from the fixed sulfamate–chloride bath is subject to the pulse frequencies and current densities. The frequencies varied from 0 to 100 Hz and current densities varied from 1 to 20 ASD (ampere per square decimeter). The Co composition has no significant variation in pulse electrodeposition but it is greatly influenced by current densities from 22.53% at 1 ASD decreased to 13.39% at 20 ASD under DC codeposition. The mean hardness of Ni–Co films has no eminent change at a pulse frequency of 10–100 Hz but it decreases with current densities from 8.72 GPa (1 ASD) to 7.13 GPa (20 ASD). The smoother morphology can be obtained at higher pulse frequency or lower current density. Good Ni–Co films with high hardness and smooth morphology can be obtained by reducing current density and increasing pulse frequency.